Flexural properties of wood cement board fabricated from cropping wastes of urban trees in a Nigerian University (2011)
The study was undertaken to investigate the possibilities of producing cement bonded particle boards from wood wastes generated From 3 urban wood species in University of Ibadan with a view to evaluating the bending properties of cement boards so produced. The materials used for the boards’ fabrication were wood wastes of Gmelina arborea, Delonix regia, Samena sena, Ordinary Portland Cement (OPC), water and calcium chloride. The bending properties evaluated are the Modulus of rupture (MOR) and Modulus of Elasticity (MOE). Data collected were subjected to analysis of variance (ANOVA) at 0.05 probability level. Results showed that the mean MOR values obtained from the fabricated boards ranged From 3.71N/mm2 to 16.63N/mm2 while the mean MOE recorded ranged from 1450.8N/mm2 to 66654.9Nmm2. The highest mean MOR was recorded from the boards produced with Gmelina arborea but Samena sena produced the strongest boards. Stronger and stiffer boards were obtained at increasing levels cement/wood mixing ratio. The effect of wood species, mixing ratio levels and interaction were significantly different at 5% significant level.